2020
DOI: 10.1002/cssc.201902761
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective β‐Arylation of α‐Angelica Lactone through Isomerization/Addition under Mild Conditions

Abstract: The conversion of biomass‐based platform molecules into various high‐value chemicals greatly promotes the utilization of renewable biomass resources. Herein, an example of Rh‐catalyzed β‐arylation of levulinic‐acid‐derived α‐angelica lactone was reported, providing the γ‐lactone‐structure products with high regioselectivity. Both arylboronic and alkenylboronic acids could be applied in this transformation. This reaction tolerated a variety of synthetically important functional groups. Moreover, the obtained γ‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Although a versatile reactivity of α-angelica lactone has already been demonstrated in the synthesis of various alkyl levulinates, 60 cellulose esters, 61 γ-butyrolactones, 62,63 α-aminoγ-ketopimelates, 64 chiral γ-alkenyl butenolides, 65,66 as well as 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles, 67,68 only scare data concerning enzyme-catalyzed reactions can be found in the literature. 69−71 Moreover, to our best knowledge, none of the reports focused on the α-angelica lactone as "neutral-washable" acyl donor used in the separation of enantiomers from a bio-resolution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a versatile reactivity of α-angelica lactone has already been demonstrated in the synthesis of various alkyl levulinates, 60 cellulose esters, 61 γ-butyrolactones, 62,63 α-aminoγ-ketopimelates, 64 chiral γ-alkenyl butenolides, 65,66 as well as 2-amino-4-(2-furanone)-4H-chromene-3-carbonitriles, 67,68 only scare data concerning enzyme-catalyzed reactions can be found in the literature. 69−71 Moreover, to our best knowledge, none of the reports focused on the α-angelica lactone as "neutral-washable" acyl donor used in the separation of enantiomers from a bio-resolution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although a versatile reactivity of α-angelica lactone has already been demonstrated in the synthesis of various alkyl levulinates, cellulose esters, γ-butyrolactones, , α-amino-γ-ketopimelates, chiral γ-alkenyl butenolides, , as well as 2-amino-4-(2-furanone)-4 H -chromene-3-carbonitriles, , only scare data concerning enzyme-catalyzed reactions can be found in the literature. Moreover, to our best knowledge, none of the reports focused on the α-angelica lactone as “neutral-washable” acyl donor used in the separation of enantiomers from a bio-resolution. Notably, our strategy was to employ α-angelica lactone, and not the levulinic acid ( LA ) or its aliphatic esters LAE , since the existing enol functionality among α - AL ’s inner structure should guarantee irreversibility of the reaction as the resultant enolate (enol-isomer) rapidly tautomerizes in situ into a more stable methyl ketone (keto-isomer), which is unable to react in the opposite direction, thus shifting the reaction’s equilibrium toward product formation (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic kinetic resolution (DKR) in asymmetric synthesis has been proven to be an ideal method of preparing enantioenriched products from racemic substrates, and it consists of racemization of a chiral substrate and kinetic resolution of the racemized substrate. Recently, Johnson reported a novel DKR in the rhodium-catalyzed asymmetric arylation of achiral γ-alkyl α-angelica lactones, giving β,γ-disubstituted γ-butyrolactones with high enantio- and trans-selectivity, where the racemization of chiral α,β-unsaturated lactone takes place through its equilibration with an achiral alkenyl ester (Scheme a). Here, we report a lactam version of the same type of DKR. In addition to the high synthetic utility of the arylated lactam products, the present reaction has an advantage over the lactone version in that an appropriate choice of the substituents on the lactam nitrogen would give us a chance to attain high efficiency in the DKR by controlling the racemization rate as well as the reactivity and enantioselectivity at the rhodium-catalyzed arylation. We found that the use of Boc (COO t -Bu) as a protecting group on the lactam nitrogen together with a chiral diene ligand L1a on the rhodium catalyst enabled the DKR in the asymmetric conjugate arylation/alkenylation of γ-substituted α,β-unsaturated γ-lactams ( rac - 1 ) to proceed with high efficiency in all aspects (Scheme b).…”
mentioning
confidence: 99%
“…As shown in Scheme a, butenolides can undergo isomerization in the presence of a catalyst or a base, providing the opportunity for DKR. Electrophilic α/γ-selectivity , has been well investigated; however, nucleophilic β-selectivity has rarely been explored . To the best of our knowledge, asymmetric alkenylation at any position remains unrealized and remains a challenge.…”
mentioning
confidence: 99%